SMOKING AS A RISK FACTOR OF CARDIOVASCULAR AND CEREBROVASCULAR DISEASES: PREVALENCE, IMPACT ON PROGNOSIS, POSSIBLE SMOKING CESSATION STRATEGIES AND THEIR EFFECTIVENESS. Part 1. Smoking Prevalence and Impact on Prognosis - O. D. Ostroumova; A. A. Izvekov; N. Yu. Voevodina (Столичная издательская компания, 2017)
The prevalence of smoking in the Russian Federation is 27.7%. Losses of potential years of life in working age associated with premature death due to smoking in Russia on average are 9 years for men, for women - 5.6 years. Tobacco use is a risk factor for 6 of 8 main causes of death in the world: ischemic heart disease (IHD); cerebral circulation disorders; lower respiratory tract infection; chronic obstructive pulmonary disease; tuberculosis; trachea, bronchus, and lung cancer. The risk of developing IHD in smoking patients is increased by 2-4 times in men and women and in any age group. Myocardial infarction occurs in smoking patients at a younger age, and they have a similar risk of coronary events with patients of older age groups. The increased risk of recurrent coronary events persists with the continuation of smoking in the patient after myocardial infarction. Smoking is associated with a double risk of ischemic stroke and a 2-4-fold increase in the risk of subarachnoid hemorrhage. The risk of peripheral arteries diseases in smokers is increased 3-6 times than this in non-smokers. The mechanisms of development of acute cardiovascular events during smoking include the activation of inflammation, platelet aggregation/thrombogenesis, the sympathetic nervous system, and the development of endothelial dysfunction due to exposure to tobacco smoke components.